Role of IASLIC in Developing Computer Skills Among LIS Professionals in India - Satpathi, JN; Satpathi, Chitra; Ghosh, Gurudas (Bangladesh Journal of Library and Information Science, 2012)
Indian Association of Special Libraries & Information Centres (IASLIC) is a pioneer association in India that has been working for the development of library and information services since its inception in 1955. IASLIC has adopted various multifaceted activities for the healthy growth of library services and to safeguard the interest of library professionals as well as library users. IASLIC has been working to resolve various discrepancies particularly in selection of hardware and library software packages, interchange formats, training for digitization and to set a standard that ideally suits the most of the libraries in our country. After introduction of computer applications in LIS in the later part of 1980s, libraries urgently required adequate computer trained workforce to perform library services. Understanding the scenario and anticipating the future needs, IASLIC has been giving prime importance to manpower development programme. A brief overview of IASLIC activities like Conferences, Seminars, Workshops, Study Circles, Special Interest Groups, publications, lectures by experts, etc. related to computer training organized by IASLIC and its role as a advisory organization to Government for making policies related to LIS has also described in this article. Bangladesh Journal of Library and Information Science Vol.2(1) July 2012 pp.39-47 DOI: http://dx.doi.org/10.3329/bjlis.v2i1.12917